Semiloka Pengabdian dalam Rancang Bangun Model Deep Learning untuk Penguatan Pembelajaran Keagamaan yang Inklusif dan Moderat - Effendi, Muhamad Ridwan; Narulita, Sari; Barnansyah, Rudi Muhammad; Nastiar, Muh Fauzan; Salsabila, Ma'wah; Sanusi, Sobar; Oktovia, Irma (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Deep learning is a model of development from Merdeka Belajar Curriculum that focuses on students' deep understanding and critical thinking, not just memorisation. The three main components are Mindful Learning, Meaningful Learning, and Joyful Learning. However, many educators, including Islamic Religious Education teachers, still experience difficulties implementing it due to a lack of training. This service activity introduces the deep learning approach to PAI teachers in PGRI and AGPAII Bojong District, Purwakarta. The methods used include interactive training and case studies to provide practical understanding. The results of this activity are training modules and practice guides that can be applied in schools. The evaluation showed that 57.1% of participants had never attended a similar workshop, 78.6% planned to implement it in their learning, and 100% recommended repeating this activity. Thus, this activity has a positive impact, changing the understanding of PAI teachers and increasing good practices in deep learning in the community.